If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(ax + b) + 3 = x (ax * 2 + b * 2) + 3 = x (2ax + 2b) + 3 = x Reorder the terms: 3 + 2ax + 2b = x Solving 3 + 2ax + 2b = x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 2ax + -3 + 2b = -3 + x Reorder the terms: 3 + -3 + 2ax + 2b = -3 + x Combine like terms: 3 + -3 = 0 0 + 2ax + 2b = -3 + x 2ax + 2b = -3 + x Add '-2b' to each side of the equation. 2ax + 2b + -2b = -3 + -2b + x Combine like terms: 2b + -2b = 0 2ax + 0 = -3 + -2b + x 2ax = -3 + -2b + x Divide each side by '2x'. a = -1.5x-1 + -1bx-1 + 0.5 Simplifying a = -1.5x-1 + -1bx-1 + 0.5 Reorder the terms: a = 0.5 + -1bx-1 + -1.5x-1
| -5j^2+2j+5=0 | | 10-1x=20+5x | | 13x+5=50 | | 6y^2-7=0 | | y=-4(x-3) | | y=-4x(x-3)(x+2)(2x-1) | | 5s^2-7=0 | | -5d^2-7d-2=0 | | -2w^2+7w-1=0 | | A=3.14(10) | | -1000/8= | | (-10)(-10)(-10)= | | A=3.14(10)2 | | 3x+10=2x-50 | | (3c-7)(2c-5)= | | 2m+6n+4m+8n= | | 37-29=4 | | 2x-4=2(5+x) | | -80+360= | | =12+6(8m-3) | | (90)(-4)= | | 4yx^4*2x^2y^5=0 | | 13/9x2/3 | | 4xy*3xy^5*4x^4y^2=0 | | 4m^2*n=0 | | x-.3x=8000 | | x/43=-75-87 | | 3x-5*2=15 | | x^3y^5*x^5y^4=0 | | 10k^2-13k-9=0 | | 25+5x=x | | 8x^3-25x^2+18x=0 |